Thrombus Composition and Success of Thrombectomy in Acute Ischemic Stroke Patients: A Histopathological Analysis. - Gurkas, Erdem; Asif, Ahmer; Akpinar, Cetin K.; Shoukat, Maryum; Aytac, Emrah; Aydin, Makbule C.; Qureshi, Adnan, I (Lippincott Williams & Wilkins, 2019)
[Abstract Not Available]
American-Heart-Association/American-Stroke-Association International Stroke Conference / State-of-the-Science Stroke Nursing Symposium -- FEB 06-08, 2019 -- Honolulu, HI